Critical social perspectives in forest and landscape restoration – a systematic review - Shelton, Madeline R.; Kanowski, Peter J.; Kleinschmit, Daniela; Ison, Ray L. (Frontiers in Environmental Science, 2024)
In response to increasing calls for better consideration of social dimensions in Forest (and) Landscape Restoration (FLR), this systematic literature review identifies and synthesises relevant themes associated with critical social perspectives in FLR. Critical perspectives are methodologically diverse but generally share an intention to interrogate power and knowledge, challenge the ‘status quo’ and ‘taken-for-granted’ assumptions, alongside promoting social justice. Critical perspectives therefore play a key role in illuminating complex social dimensions in global environmental governance. This review asks: What is the role of critical social perspectives within the academic discourse on FLR, and what key insights about FLR have these perspectives provided over the period 2000–2023? A total of 449 relevant academic papers were published during this period. An initial assessment of the abstracts, title and keywords found social dimensions were addressed in some way, even if only negligibly, in 211 of the 449 papers, and themes associated with critical social perspectives were evident in only 40 papers. These 40 papers were then read in full, and six key topic areas emerged: 1) Assumptions underpinning the links between FLR and human-wellbeing, particularly the tendency to measure human-wellbeing using simple economic indicators, were challenged as naïve and potentially misleading; 2) Tenure issues appear to be frequently under-appreciated, with serious consequences such as displacement of communities; 3) Top-down, technocratic models of governance are problematised for neglecting the socio-political contexts of FLR, which are laden with value and power asymmetries, as well as the implications of historical legacies (e.g., colonialism); 4) While there has been a proliferation of discursive intent to better ‘engage local stakeholders’, doing so remains opaque in principle and practice; 5) The heterogeneity of ‘local stakeholders’ emphasises the need to consider multiple intersections of social identities and diversity, and attend to gendered dimensions of FLR; 6) Accepting epistemological pluralism is considered fundamental to incorporating local and Indigenous Peoples’ knowledges into more people-centred, locally-relevant FLR governance and practice. The review concludes that, if FLR is to genuinely pursue the imperative to enhance human-wellbeing alongside the goal of regaining ecological integrity, a recalibration of research priorities toward interdisciplinary social sciences, and better representation of locally-situated stakeholders, are required. This will involve deliberation between researchers, from both social and natural sciences, as well as practitioners; and making concerted efforts to steer away from simplistic framings of the issues, toward more nuanced understandings of and responses to the systemic complexities embedded in FLR.